2014
DOI: 10.3390/ijerph110909217
|View full text |Cite
|
Sign up to set email alerts
|

Application of Magnesium Modified Corn Biochar for Phosphorus Removal and Recovery from Swine Wastewater

Abstract: The recycling of lost phosphorus (P) is important in sustainable development. In line with this objective, biochar adsorption is a promising method of P recovery. Therefore, our study investigates the efficiency and selectivity of magnesium modified corn biochar (Mg/biochar) in relation to P adsorption. It also examines the available P derived from postsorption Mg/biochar. Mg/biochar is rich in magnesium nanoparticles and organic functional groups, and it can adsorb 90% of the equilibrium amount of P within 30… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
98
2
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 215 publications
(107 citation statements)
references
References 33 publications
6
98
2
1
Order By: Relevance
“…It has been shown that biochar has good adsorption effect on typical pollutants of livestock wastewater such as organic pollutants [10], heavy metals [14], nitrogen, and phosphorus [11]. After magnetization, biochar with good magnetic is easily separated from liquid [15], which is more suitable for livestock wastewater, compared to commercial activated carbon products.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been shown that biochar has good adsorption effect on typical pollutants of livestock wastewater such as organic pollutants [10], heavy metals [14], nitrogen, and phosphorus [11]. After magnetization, biochar with good magnetic is easily separated from liquid [15], which is more suitable for livestock wastewater, compared to commercial activated carbon products.…”
Section: Introductionmentioning
confidence: 99%
“…Zhang et al [47] found the biochar had a good adsorption effect on ammonia nitrogen, while the adsorption of phosphate was very weak. Fang et al [11] modified corncob biochar with magnesium salt, so that the surface electricity of biochar was positive, which enhanced its phosphate adsorption efficiency.…”
Section: Surface Electrical Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…This oxidation is useful to improve surface functional groups of biochar. For example, oxidation using HNO 3 C=O, and COOH [9]. The other researcher reported that oxidation by HNO 3 improves carboxylic [10].…”
Section: Introductionmentioning
confidence: 99%
“…Biochar is one of porous material adsorbents which has potential for adsorption of metal cations such as Pb, Cd, Ni, and Cu [1], Zn [1,2], anion such as phosphate [3] or arsenic (V) [2], and organic substances such as humic and tannic acid [4], trimethyltin [2], various antibiotics [5]. Combination of biochar using various metal oxides can improve performance of biochar in adsorption [6,7,8].…”
Section: Introductionmentioning
confidence: 99%